"التعليل بالانقطاع عند الإمام علي بن المديني من خلال كتابه (علل الحديث ومعرفة الرجال والتاريخ) -دراسة تأصيلية تطبيقية- " - عشيري, كريمة (University of Eloued جامعة الوادي, 2018)
"يتناول هذا البحث دراسة منهجية الإمام علي بن المديني في التعليل بالانقطاع، وذلك من خلال تتبع الباحثة لعباراته وأقواله في كتابه (علل الحديث ومعرفة الرجال والتاريخ)، ودراستها وذلك للوقوف على منهجه في التعليل بظاهرة انقطاع السند. وقد بيَّنت الدراسة أن مفهوم العلة عند الإمام ابن المديني شامل للعلل الظاهرة والخفية على حدٍ سواء، كما أبرزت الوسائل التي استخدمها عند كشفه للعلة، وأظهرت أن منهج ابن المديني في التعليل ليس له قاعدة مطردة، ولكنه يُعلل الأحاديث بحسب القرائن التي استخدمها، كما أنه ركز على شرط اتصال السند في كتابه، وسماع الرواة من بعضهم البعض، أو عدمه، لما له من أهمية في نظره، كما كشفت عن طريقته في تعليل السند، فكان لا يكتفي لإثبات الاتصال بين الرواة في الإسناد المعنعن بحصول السماع وحسب، بل كان يأخذ باللقاء والرؤية وغيرهما إذا توفرت القرائن القوية الدالة على ترجيح الاتصال فيها، والإمام علي بن المديني إمام له باع طويل في مجال تعليل الأحاديث، وهذا ما شهد له به أهل الفن والصنعة. " "Abstract This research deals with the methodological study of Imam Ali ibn al-Madaini in explaining the disconnection, by following the researcher to his expressions and his sayings in his book (Alal Hadith and knowledge of men and history) and study it in order to stand on his method in explaining the phenomenon of breakage of the bond. The study has shown that the concept of the bug in Imam Ibn al-Madinah is comprehensive for both apparent and hidden causes. He also highlighted the methods used in uncovering the problem. He showed that Ibn al-Madinah's approach to reasoning has no consistent basis. He explains the hadiths according to the clues he used. On the condition of the connection of the bond in his book - the subject of study and research - and to hear the narrators of each other, or not, because of the importance in his view, as revealed his way to explain the bond, was not enough to prove the connection between narrators in the attribution Almnn hearing only, Balkan takes the meeting and vision and others if there is strong evidence E on the weight of communication in them. Imam Ali ibn al-Madaini is an imam who has a long tradition in the field of explanation of monotheism, and this is what has been witnessed by the people of art and workmanship. "
مذكرة ماستر تخصص علوم الحديث
Keywords: علي بن المديني، الانقطاع، التعليل، علل الحديث، معرفة الرجال; Ali ibn al-Madaini, interruption, reasoning, talk, knowledge of men